Les pouvoirs de l'administration fiscale dans la perception et le recouvrement de l'impôt : mythes et réalités - Louit, Christian (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
This article deals with the powers of the fiscal administration in French law. The author examines the various protections afforded by the law and the administration to the taxpayer. The author also studies the powers of the administration in relation to the reassestment of tax. Such procedures are either contradictory or discretionnary. The taxpayer's rights are guaranteed by certain rules concerning limitation of actions and changes in official policis.